2013
DOI: 10.1063/1.4816484
|View full text |Cite
|
Sign up to set email alerts
|

First-principles thermodynamic screening approach to photo-catalytic water splitting with co-catalysts

Abstract: We adapt the computational hydrogen electrode approach to explicitly account for photo-generated charges and use it to computationally screen for viable catalyst/co-catalyst combinations for photo-catalytic water splitting. The hole energy necessary to thermodynamically drive the reaction is employed as descriptor for the screening process. Using this protocol and hybrid-level density-functional theory we show that water oxidation on bare TiO 2 surfaces is thermodynamically more complex than previously thought… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…In this model, the limiting potential (U L )i sd efined as the appliedp otential (U)r equired such that every step in the assumed mechanism is exergonic. Limitingp otentials correlate well with experimental activities for av ariety of reductivea nd oxidative reactions involvingp roton transfer, [24][25][26] and we also use the limiting potentialfor N 2 reduction in this study.…”
Section: Dft Methods For Electrochemical N 2 Reductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this model, the limiting potential (U L )i sd efined as the appliedp otential (U)r equired such that every step in the assumed mechanism is exergonic. Limitingp otentials correlate well with experimental activities for av ariety of reductivea nd oxidative reactions involvingp roton transfer, [24][25][26] and we also use the limiting potentialfor N 2 reduction in this study.…”
Section: Dft Methods For Electrochemical N 2 Reductionmentioning
confidence: 62%
“…[22] Free-energyc orrections to the electronic energy were obtained by using standard vibrational corrections in the harmonic approximation to the enthalpy and entropy, and freeenergy corrections to gas-phase H 2 and N 2 are also included. Limitingp otentials correlate well with experimental activities for av ariety of reductivea nd oxidative reactions involvingp roton transfer, [24][25][26] and we also use the limiting potentialfor N 2 reduction in this study. [23] The CHE uses one-half of the chemical potential of hydrogen as the chemical potential of the proton-electron pair,a st hese two species are, by definition, in equilibrium at 0V versusareversible hydrogen electrode (RHE).…”
Section: Dft Methods For Electrochemical N 2 Reductionmentioning
confidence: 63%
“…In 2013, Oberhofer and Reuter used the hole energy required for thermodynamically driving the reaction as the descriptor for the computational screening of TiO 2 photocatalytic water splitting systems with cocatalysts . They found that TiO 2 loaded with small Au clusters are more energetically favorable for water oxidation than pure TiO 2 surfaces or an extended Au(111) surface because unsaturated metal atoms often act as the active sites of surface reaction.…”
Section: Loading Optimal Cocatalystsmentioning
confidence: 99%
“…doublet for OH and OOH, and triplet for O. This is an important issue, as most semi-local functionals yield the wrong spin-polarization for the O adsorbate, and already due to this produce a large deviation in the corresponding binding energy with respect to the higher-rung calculations 67 . Similar to the findings made for the zeolitic system, tier2 basis sets readily converge all E b to within 10 meV at the semi-local and hybrid level, while at the double-hybrid level the valence-correlation consistent NAO-VCC-4Z basis set for all O atoms together with a counterpoise correction 50 was required to reach this level of convergence.…”
Section: B Water Splitting Reaction Energetics At Tio 2 (110)mentioning
confidence: 99%